Learning modular policies for robotics - Neumann, Gerhard; Daniel, Christian; Paraschos, Alexandros; Kupcsik, Andras; Peters, Jan (Frontiers in Computational Neuroscience, 2014)
A promising idea for scaling robot learning to more complex tasks is to use elemental behaviors as building blocks to compose more complex behaviour. Ideally, such building blocks are used in combination with a learning algorithm that is able to learn to select, adapt, sequence and co-activate the building blocks. While there has been a lot of work on approaches that support one of these requirements, no learning algorithm exists that unifies all these properties in one framework. %Adaptation of the parameter vector is needed to reuse the elemental behaviours for more than one situation. %Second, the learning architecture needs to learn to select between and to sequence such parametrized building blocks. Finally, %the expressibility of a modular control architecture can be drastically increased if the architecture supports co-activate the single building blocks. %In this paper we give an overview of our work on learning such a modular control architecture. In this paper we present our work on a unified approach for learning such a modular control architecture. We introduce new policy search algorithms that are based on information-theoretic principles and are able to learn to select, adapt and sequence the building blocks. Furthermore, we developed a new representation for the individual building block that support co-activation and principled ways for adapting the movement. Finally, we summarize our experiments for learning modular control architectures in simulation and with real robots.